2020
DOI: 10.1164/rccm.201905-0973oc
|View full text |Cite
|
Sign up to set email alerts
|

FSTL-1 Attenuation Causes Spontaneous Smoke-Resistant Pulmonary Emphysema

Abstract: Rationale: The role of FSTL-1 (follistatin-like 1) in lung homeostasis is unknown.Objectives: We aimed to define the impact of FSTL-1 attenuation on lung structure and function and to identify FSTL-1-regulated transcriptional pathways in the lung. Further, we aimed to analyze the association of FSTL-1 SNPs with lung disease.Methods: FSTL-1 hypomorphic (FSTL-1 Hypo) mice underwent lung morphometry, pulmonary function testing, and microcomputed tomography. Fstl1 expression was determined in wildtype lung cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Osteopontin interacts directly with α4- and α9β1 integrins to promote tumor cell invasion ( 104 ), with the alternatively spliced C-terminally truncated form of the protein being particularly pro-invasive ( 105 ). Follistatin-like protein 1, which regulates alveolar maturation in the developing lung by inhibiting BMP4/SMAD1/3/5 signaling ( 106 ) and inhibits emphysema development in response to injury ( 107 ) also binds directly to pro-osteopontin to prevent its proteolytic activation and thus inhibit lung cancer metastasis. This likely underpins why the expression of follistatin-like 1 protein is downregulated in NSCLC and low expression of this protein is associated with poor survival ( 101 ).…”
Section: The Role Of the Ecm In Primary And Secondary Dormancy Dynamimentioning
confidence: 99%
“…Osteopontin interacts directly with α4- and α9β1 integrins to promote tumor cell invasion ( 104 ), with the alternatively spliced C-terminally truncated form of the protein being particularly pro-invasive ( 105 ). Follistatin-like protein 1, which regulates alveolar maturation in the developing lung by inhibiting BMP4/SMAD1/3/5 signaling ( 106 ) and inhibits emphysema development in response to injury ( 107 ) also binds directly to pro-osteopontin to prevent its proteolytic activation and thus inhibit lung cancer metastasis. This likely underpins why the expression of follistatin-like 1 protein is downregulated in NSCLC and low expression of this protein is associated with poor survival ( 101 ).…”
Section: The Role Of the Ecm In Primary And Secondary Dormancy Dynamimentioning
confidence: 99%
“…Given that our work and others indicated Nr4a1 -/macrophages had a dysregulated tolerization phenotype, it was unexpected that Nr4a1 -/macrophages retained K. pneumoniae killing ability (18). Despite genetic profiles noting that Nr4a1 is induced in neutrophils in response to inflammatory stimuli, no prior work has determined what role Nr4a1 has in the neutrophil response, and the finding that Nr4a1 is critically important in neutrophils, and not macrophages, has not been previously reported (30,31).…”
Section: Discussionmentioning
confidence: 52%
“…While some genes were unchanged, reduced lung expression of the innate pro-inflammatory cytokines, Il1b and Il6, as well as the neutrophil recruitment chemokine, Cxcl2, 5 hours after infection suggested an innate phagocyte response pathway defect (32). Several disease models have shown that macrophage or monocyte expression of NR4A1 has significant impact on inflammation in models of cardiovascular disease, LPS-induced sepsis, and fibrosis (6,7,17,18,33,34). However, in each of these models, NR4A1 modulated macrophage inflammatory genes in response to insult or the deletion of Nr4a1 resulted in an exaggerated macrophage inflammatory phenotype, while we observed reduced pro-inflammatory cytokines in K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, FSTL1 can induce EMT and airway remodeling in asthma 34 . Several FSTL1 SNPs were found corresponded to COPD and lung function, and FSTL-1 de ciency might protect mice from cigarette smoke induced emphysema 35 . In the present study, we further unravel the role of FSTL1 in the pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%